The Impact of Road Construction on Subjective Well-Being in Communities in Madre de Dios, Peru - Riley-Powell, Amy R. (Int J Environ Res Public Health, 2018)
The interoceanic highway (IOH) in Madre de Dios, Peru has driven dramatic change in the Peruvian Amazon basin. We conducted a mixed methods study to examine the impact of these changes on the subjective well-being (SWB) of four communities on the IOH. Themes that emerged qualitatively included changing health threats, environmental degradation, and the impact of increased migration. To achieve a higher level of SWB, respondents emphasized the need for higher incomes, opportunities to learn new skills, and a better education for their children. Potential threats to SWB included marital problems and poorer health. Quantitative analyses suggested that social support and a sense of security impacted reported SWB scores based on life satisfaction, and the impact of income on life satisfaction was mediated by food security. Although long-term residents felt that specific determinants of SWB had both increased (food variety, transport and access to work) and decreased (access to natural resources and hunting), the majority reported that their lives had improved overall. Health had been affected by the IOH in both negative ways (increased dengue and road accidents) and positive ways (improved access to health services). Our results suggest that the rapidly-changing communities near the IOH link well-being to health, income, community, and the environment.